2020
DOI: 10.46991/pysu:b/2020.54.1.055
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Carbon Sources Mixture (Glucose, Glycerol and Formate) and Generation of Fermentation End-Products by $Escherichia$ $Coli$

Abstract: In this study anaerobic utilization of mixed carbon sources (glucose, glycerol, formate) and generation of fermentation end-products by Escherichia coli at slightly alkaline and slightly acidic pHs was investigated at the first time. It has been shown that E. coli is able to perform co-fermentation of glucose and glycerol in the presence of external formate. The latter was utilized by bacterial cells at first. Acetate is the permanent product (25–50 mM) during both glucose and glycerol utilization. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…As glycerol fermentation extended reasonably later in wt, the quantitative and qualitative difference between end-products from glucose and glycerol at pH 7.5 reported being apparent. 4 High concentration ethanol (22-80 mM) was observed starting from 2 hr in fhlA mutant (2-240 hr) at pH 7.5 (see Figure 2b), which was directly related to the earlier fermentation of glycerol. 9 These amounts were mentioned in the wt later when the main utilization of glycerol was observed hr; see Figure 2a).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…As glycerol fermentation extended reasonably later in wt, the quantitative and qualitative difference between end-products from glucose and glycerol at pH 7.5 reported being apparent. 4 High concentration ethanol (22-80 mM) was observed starting from 2 hr in fhlA mutant (2-240 hr) at pH 7.5 (see Figure 2b), which was directly related to the earlier fermentation of glycerol. 9 These amounts were mentioned in the wt later when the main utilization of glycerol was observed hr; see Figure 2a).…”
Section: Resultsmentioning
confidence: 85%
“…3.1 | Specific growth rate, substrates utilization, and fermentation end-products generation during fermentation of mixed carbon sources in wt and fhlA mutant strain E. coli bacteria utilize the mixture of different carbon sources in the absence of external electron acceptors, which was shown previously. 4,5,7,8,19 It is important to study the role of proton ATPase on cell specific growth rate (μ), as F O F 1 is one of the main Δp generators and all bacteria require Δp to grow and remain viable under replicating and non-replicating conditions. [34][35][36] To reveal the role of F O F 1 on μ DCCD was applied and it was shown that μ was impaired by DCCD 50% in wt at pH 7.5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations